PENERAPAN STRATEGI PEMBELAJARAN INTEGRATED TERHADAP KREATIVITAS BELAJAR MAHASISWA PADA MATA KULIAH ORGANISASI DAN EKSTRAKURIKULER - SABRINA HARAHAP (LP2MTBM MAKARIOZ, 2019)
Conditions that are not conducive to learning have an impact on difficult to develop opinions, (difficult to find ideas or ideas the purpose of this study is to find information about the Effects of the Implementation of Integrated Learning Strategies on Student Learning Creativity in Organizational and Extracurricular Subjects. The research method used in this study is experimental method The form of experimental research used was pre-experimental.The research design used was One Group Pretest-Posttest Design, which is a design that uses one group of subjects.The data collection tool in the form of tests before (pretest) and after (posttest) Tests selected in this study is a pre-test and a post-test in the form of multiple choice.Technics of data analysis used culaitative data analysis.The results in this study are the application of integrated learning strategies can increase and provide a significant influence facing student learning creativity in Organizational and Extracurricular Courses. Student learning creativity before being given an integrated learning strategy in Organizational and Extracurricular subjects is sufficient that is 44.1 with a standard deviation of 9.65 and student learning creativity after applying an integrated learning strategy is good which is 67 with a standard deviation of 11.5.